Embracing "Elsewhereness": May Agnes Fleming and Late Nineteenth-Century Transatlantic Authorship - Dorward, Sarah (Papers of the Bibliographical Society of Canada / Cahiers de la Société bibliographique du Canada, 2025)
Authorship in Canada during the nineteenth century was fundamentally transatlantic. Authors who resided in British North America, and later Canada, needed to navigate the system of trans-border publishing if they wished to see much in the way of financial compensation or wide readerships. While the material and legal conditions of trans-border publishing were a hindrance to many authors residing in Canada, some were able to negotiate these conditions to their advantage. One such author is May Agnes Fleming, a New Brunswick-born writer whose literary career was made possible through her pursuit of trans-border — and eventually transatlantic — publishing. In this article, I explore how Fleming’s accrual of mass-market, transatlantic readers and subsequent significant financial success was born by this period’s international copyright agreements. Using Fleming as a case study, this article encourages us to challenge our perceptions of nineteenth-century publishing conditions as exclusively an obstacle to authorship, instead making room for authors who cannily negotiated these conditions in an exceptional, intentional way.